PENETAPAN SANKSI PIDANA PELAKU PENIPUAN DI PENGADILAN NEGERI BATANG PERSPEKTIF HUKUM PIDANA ISLAM - Yulianingsih, Ayu Putri; Suciyani, Suciyani (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Abstract This study aims to find out the basis of the judge's considerations in imposing a sentence on the decision Number: 210/Pid.B/2019/Pn.Btg. and to find out the analysis of the decision Number: 210/Pid.B/2019/Pn.Btg. from the perspective of Islamic criminal law. The problem studied is the judge's consideration in deciding the case Number: 210/Pid.B/2019/Pn.Btg. and judges' considerations in Islamic criminal law. This type of research is library research and the data sources are taken from secondary data sources and tertiary data sources. The method of data collection is done by documentation research techniques. The results of this study found that the basis for the judge's consideration in deciding criminal sanctions against perpetrators of fraud in Decision Number 210/Pid.B/2019/PN Btg in this case was that the defendant's actions had fulfilled the elements of fraud in accordance with Article 378 of the Criminal Code, had a form of error. Which is intentional and also there is no justification and forgiving reason. The sanction imposed by the panel of judges is that the defendant is charged with Article 378 of the Criminal Code, with imprisonment for 10 (ten) months and is required to pay court fees. In the perspective of Islamic Criminal Law, the judge's consideration in deciding the criminal case of fraud in Decision No. 210/Pid.B/2019/PN.Btg is in accordance with the elements in the Criminal Law and Islamic Criminal Procedure Code, which are subject to sanctions with imprisonment and imprisonment ta'zir. Because fraud does not fulfill one of the elements of the determination of criminal sanctions for theft in Islamic criminal law. Keywords: Fraud; Law; Sanctions. Abstrak Penelitian ini bertujuan untuk dapat mengetahui dasar pertimbangan hakim dalam menjatuhkan hukuman pada putusan Nomor: 210/Pid.B/2019/Pn.Btg., serta untuk mengetahui analisis putusan Nomor: 210/Pid.B/2019/Pn.Btg. dari perspektif hukum pidana Islam. Permasalahan yang diteliti yaitu pertimbangan hakim dalam memutus perkara Nomor: 210/Pid.B/2019/Pn.Btg.dan pertimbangan hakim dalam hukum pidana Islam. Jenis penelitian ini adalah studi kepustakaan (library research) dan sumber data yang diambil dari sumber data sekunder dan sumber data tersier. Metode pengumpulan data dilakukan dengan teknik penelitian dokumentasi. Hasil penelitian ini didapatkan bahwa dasar pertimbangan hakim dalam memutus sanksi pidana terhadap pelaku penipuan dalam Putusan Perkara Nomor 210/Pid.B/2019/PN Btg dalam kasus ini adalah perbuatan terdakwa telah memenuhi unsur-unsur penipuan sesuai dengan Pasal 378 KUHP, memiliki suatu bentuk kesalahan yang berupa kesengajaan dan juga tidak ada alasan pembenar dan pemaaf. Sanksi yang dijatuhkan majelis hakim yaitu terdakwa dijerat Pasal 378 KUHP, dengan pidana penjara selama 10 (sepuluh) bulan serta diharuskan membayar biaya perkara. Dalam Perspektif Hukum Pidana Islam pertimbangan hakim dalam memutuskan perkara pidana penipuan dalam Putusan Perkara No.210/Pid.B/2019/PN.Btg adalah telah sesuai dengan unsur-unsur dalam Hukum Pidana dan Hukum Acara Pidana Islam, yang mana penipuan tidak memenuhi salah satu unsur dari penetapan sanksi pidana pencurian. Maka dikenakan sanksi dengan hukuman jarimah ta'zir. Kata Kunci: Hukum; Penipuan; Sanksi.